A new nursing pattern based on ERAS concept for patients with lumbar degenerative diseases treated with OLIF surgery: A retrospective study - Lu, Hai-rong; Yang, Ao; Li, Xu; He, Meng-zi; Sun, Jia-yuan (Frontiers in Surgery, 2023)
Objective The purpose of this study was to introduce enhanced recovery after surgery (ERAS) concept into patients with lumbar degenerative diseases who were treated with oblique lumbar interbody fusion (OLIF), and to assess whether it could increase clinical efficacy, reduce perioperative complications, shorten length of hospital stay (LHS), decrease readmission rate, and improve patient satisfaction. Methods The study included patients with lumbar degenerative diseases (LDDs) who underwent OLIF between July 2017 and October 2018 (non-ERAS group), and between November 2018 and July 2020 (ERAS group). The two groups were compared according to the demographic and clinical characteristics. Results There was no significant difference in descriptive characteristics and concomitant diseases between the two groups. The preoperative Oswestry disability index (ODI) score (P = 0.191), lumbar visual analogue scale (VAS) score (P = 0.470), and leg VAS score (P = 0.657) did not significantly different. Most of the ERAS measures were also well implemented after surgery, except for early delivery (74.2%), early catheter removal (63.9%), and multimodal analgesia (80.6%). The LHS in the ERAS group was significantly shorter than that in the non-ERAS group (P = 0.004). Besides, Hamilton Anxiety Rating Scale (HAMA) score at 3 days after surgery showed a significant difference between the two groups (P = 0.019). The patient satisfaction in ERAS group was significantly higher than that in the non-ERAS group (P = 0.001). Conclusion The new nursing pattern combined with ERAS in patients with LDDs who underwent OLIF did not improve the short-term prognosis of surgery, while it could effectively reduce postoperative complications, shorten the LHS, and improve patient satisfaction, and did not lead to additional adverse events.